Penerapan Green Accounting Terhadap Nilai Perusahaan Melalui Profitabilitas pada Perusahaan Sektor Energi - Rosyad Aldi Maulana; Anna Sumaryati (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2025)
This study aims to analyze the effect of the application of green accounting on company value through profitability in the energy sector. Using a quantitative approach with test tools using WarpPLS 7.0, secondary data was collected from the annual report of 249 samples from 83 companies listed on the Indonesia Stock Exchange during 2021-2023. The results show that environmental performance has no significant effect on company value, while environmental costs and profitability have a significant influence. In addition, environmental performance and environmental costs also have a significant effect on profitability. However, profitability cannot mediate the relationship between environmental performance and environmental costs with a company's value.